Assessing comprehension of medical texts: a new approach to recall analysis - Saeed ZaREIN-Dolab (Journal of Medical Education, 2002)
Background: The comprehension processes are often inferred or explored indirectly through the assessment of the performance of the students on certain tasks. Comprehension is typically measured by the techniques in which the test taker reads a short text and then selects the correct answers in multiple choice questions, true/false and yes/no tasks or matching activities. Purpose A new approach to the analysis of recall protocols, written by medical students, is devised which is mainly based on the performance analysis. Methods Three texts have been selected out of the pool of 20 texts based on the medical students' level of familiarity content. Care was taken to select texts of the same level of readability. The language proficiency of the students was measured by English Language Battery Test (ELBA test). The students read the texts and wrote recall in their mother tongue. Half the students did the ELBA test before reading the texts and writing the recalls and the other half did the task in reverse sequence. The recall analysis, so that the emphasis is on students' performance at two levels: identification and interpretation processes. Results Identification processes and interpretation processes are interacting efficiently when a content familiar text is used. The unfamiliar text, when read by a student with prior language proficiency, is not efficiently comprehended. However, when familiar text is read by the same student, he can compensate his poor language proficiency by resorting to his prior knowledge. Conclusion Interaction between different knowledge sources are better demonstrated when recall is used as the technique for measuring reading comprehension. Keywords Recall, Language Proficiency, Medical Language, Reading